(untitled) (Fractal: Journal of Psychology, 2009)
he pleasures and difficulties of urban life are our starting point for this essay. We congregate some authors who had dealt with this subject: the ’desire of the city’, strong motivation that impel the men for the collective life, and the ’desire in the city’, the individual impulses that can make difficult the formation of this collective life. Through Sade, Calvino and Perec, we go to arrive at the Greek Polis, where the aspect politician of the collective life appeared for the first time. Since the Greeks, therefore, there is the question: how can be possible the life in the cities?